Volume and Intensity of Locomotor Activity in International Men's Field Hockey Matches Over a 2-Year Period - James, Carl A.; Gibson, Oliver R.; Dhawan, Aishwar; Stewart, Craig M.; Willmott, Ashley G. B. (Frontiers in Sports and Active Living, 2021)
The locomotor demands of international men’s field hockey matches were investigated across positions (DEF, MID, FWD) and playing quarters. Volume (i.e. total values) and intensity (i.e. relative to playing time) data were collected using 10-Hz GPS/100-Hz accelerometer units from the #11 world-ranked (WR) team, during 71 matches, against 24 opponents (WR 12±11 [range 1-60]). Mean±SD team total distance (TD) was 4861±871 m, with 25% (1193±329 m) ‘high-speed running’ (>14.5 km.h-1) and 8% (402±144 m) ‘sprinting’ (>19.0 km.h-1). Reduced TD (range: -3-4%) and average speed (range: -3.4-4.7%) occurred through subsequent quarters, versus Q1 (p<0.05). A ‘large’ negative relationship (r=-0.64) was found between playing duration and average speed. Positional differences (p<0.05) were identified for all volume metrics including; playing duration (DEF 45:50±8:00 min, MID 37:37±7:12 min, FWD 33:32±6:22 min), TD (DEF 5223±851 m, MID 4945±827 m, FWD 4453±741 m), sprinting distance (DEF 315±121 m, MID 437±144 m, FWD 445±129 m) and acceleration efforts (>2 m.s2, DEF 48±12, MID 51±11, FWD 50±14). Intensity variables similarly revealed positional differences (p<0.05) but with a different pattern between positions; average speed (DEF 115±10 m.min-1, MID 132±10 m.min-1, FWD 134±15 m.min-1), sprinting (DEF 7±3 m.min-1, MID 12±4 m.min-1, FWD 14±4 m.min-1) and accelerations (DEF 1.1±0.3 n.min-1, MID 1.4±0.2 n.min-1, FWD 1.5±0.3 n.min-1). Physical outputs reduced across playing quarters, despite unlimited substitutions, demonstrating the importance of optimising physical preparation prior to international competition. Volume and intensity data highlight specific positional requirements, with forwards displaying shorter playing durations, but greater high-intensity activities than defenders.